Marketing Mix Strategy Development for Souvenir Shops emphasize identity in Chi Thuan, Chi Thuan Sub-district, Khueang Nai District, Ubon Ratchathani Province - Yuwadeeniwet, Nareenuch; Sriwongwanna, Jaturong; Kasetiam , Vikanda (Journal for Developing the Social and Community, 2020)
The objectives of this research article were to 1) study the personal factors of Thai tourists visiting Chi Thuan, Chi Thuan Sub-district, Khueang Nai District, Ubon Ratchathani Province 2) compare the marketing mix factors of Souvenir shop, emphasizing the identity of Chi Thuan, Chi Thuan Sub-district, Khueang Nai District, Ubon Ratchathani Province Classified by personal factors 3) develop marketing mix strategies for Souvenir shop, emphasizing the identity of Chi Thuan, Chi Thuan Sub-district, Khueang Nai District, Ubon Ratchathani Province. Using questionnaires to collect data from 400 Thai tourists who visiting Chi Thuan, Chi Thuan Sub-district, Khueang Nai District, Ubon Ratchathani Province. Statistics used for data analysis were average, standard deviation, independent t-test, and One-Way ANOVA (F-test). The research result found that The majority of Thai tourists visiting Chi Thuan, Chi Thuan Sub-district, Khueang Nai District, Ubon Ratchathani Province were male, ages of 20-30 years, study bachelor's degree, and earn 5,000-10,000 baht per month. The results of the research about the comparative analysis of marketing mix factors of souvenir shop which focusing on identity of Chi Thuan, Chi Thuan Sub-district, Khueang Nai District, Ubon Ratchathani Province, classified by gender, age, education level and occupation 2.1 Different genders will affected the marketing mix factors of souvenir shop which focusing on identity of Chi Thuan, Chi Thuan Sub-district, Khueang Nai District, Ubon Ratchathani Province in all aspects, with statistical significance at the .01 level. 2.2 Different in age will not affected the marketing mix factors of souvenir shop which focusing on identity of Chi Thuan, Chi Thuan Sub-district, Khueang Nai District, Ubon Ratchathani Province in all aspects, with no statistical significance. 2.3 Different levels of education will affected the marketing mix factors of souvenir shop which focusing on identity of Chi Thuan, Chi Thuan Sub-district, Khueang Nai District, Ubon Ratchathani Province, with statistical significance at the .01 level in terms of price, memory channel and marketing promotion. 2.4 Different occupations will affected the marketing mix factors of souvenir shop which focusing on identity of Chi Thuan, Chi Thuan Sub-district, Khueang Nai District, Ubon Ratchathani Province, with statistical significance at the .01 level in all aspects. 2.5 Different monthly incomes will affected the marketing mix factors of souvenir souvenir shops focusing on the identity of Ban Chetuan, Chetuan Subdistrict, Khueang Nai District, Ubon Ratchathani Province, with statistical significance at the .01 level in term of price, distribution channel and marketing promotion. Suggestions for the marketing mix factors of souvenir souvenir shops focusing on the identity of Ban Chetuan, Chetuan Subdistrict, Khueang Nai District, Ubon Ratchathani Province should focus on the diversity of the target tourist group and create their strategy based on a variety of product development, set prices, create distribution channels and create a variety of marketing activities to accommodate the different types of tourists.